How do patients and the public understand overtesting and overdiagnosis? A protocol for a thematic meta-synthesis of qualitative research - Rachelle Buchbinder; Denise A O’Connor; Rae Thomas; Stacy Carter; Romi Haas; Tomas Rozbroj (BMJ Open)
Introduction Examining patient and public understanding of overtesting and overdiagnosis (OverTD) is vital for reducing the burden of OverTD. Studies from disparate contexts, disciplines and focusing on disparate healthcare issues have examined patient and public understanding of OverTD. A synthesis is needed to bring this literature together, examine common themes, strengthen conclusions and identify gaps. This will help steer further research, policy and practice to improve patient and public understanding of OverTD. The objective of this study is to synthesise qualitative research data about patient and public understanding of OverTD.Methods and analysis A thematic meta-synthesis will be used to synthesise primary qualitative research and qualitative components of primary mixed-methods research about patient and public understanding of OverTD. Studies published in English will be included. These will be identified using systematic searches from inception to March 2020 in the Scopus, CINAHL, PsycINFO and MEDLINE databases. Studies that satisfy eligibility criteria will be assessed for methodological quality using the Critical Appraisal Skills Programme (CASP) checklist. Thematic meta-synthesis will comprise three stages: (1) line-by-line coding; (2) generation of descriptive themes and (3) generation of analytic themes. Confidence in the synthesis findings will be assessed using the Grading of Recommendations Assessment, Development and Evaluation Confidence in Evidence (GRADE CERQual) approach. A summary of GRADE CERQual results will be presented alongside the key themes. Study eligibility screening, data extraction, analysis and the CASP and GRADE CERQual assessments will be undertaken independently by two review authors.Ethics and dissemination Ethics approval is not required for this secondary analysis of published data. The results will be disseminated in peer-reviewed journals and may be presented in conference papers and elsewhere.PROSPERO registration number CRD42020156838